2008
DOI: 10.1176/appi.ap.32.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Pakistani Medical Students Towards Psychiatry as a Prospective Career: A Survey

Abstract: Relatively small numbers of students identified psychiatry as their specialty of choice. This trend is similar to many other studies. Given the small number of practicing psychiatrists in Pakistan, this finding is not very encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Estimates of the percentage of students who consider psychiatry as a career option but have not made a definite decision vary by country and methodology, for example 9% in the UK [44], 7.6% in Pakistan [45] and 33% in Israel [46]. Our combined finding was 15%, with geographical variation ranging from 0-33%, and thus broadly in line with previous results.…”
Section: Discussionsupporting
confidence: 89%
“…Estimates of the percentage of students who consider psychiatry as a career option but have not made a definite decision vary by country and methodology, for example 9% in the UK [44], 7.6% in Pakistan [45] and 33% in Israel [46]. Our combined finding was 15%, with geographical variation ranging from 0-33%, and thus broadly in line with previous results.…”
Section: Discussionsupporting
confidence: 89%
“…While enrolled medical students in the United States find the field intellectually interesting (Cutler et al 2006), many regard clinical work with psychiatric patients as unappealing (Galka et al 2005;Martin et al 2005;Singh et al 1998;Balon et al 1999;Sierles et al 1995;Nielsen et al 1981) and even stressful (Cutler et al 2006). Similar observations have been made in many countries around the world (Brockington and Mumford 2002;Malhi et al 2002;Fischel et al 2008;Ndetei et al 2008;Syed et al 2008;Ay et al 2006).…”
Section: Introductionsupporting
confidence: 84%
“…The students noted that it was interesting to try to unravel the cause of a psychiatric illness, and that psychiatric hospitals have a specifi c contribution to make to the treatment of the mentally ill. The practice of psychiatry allowed the development of really rewarding relationships with people (Syed et al, 2008;Wigney & Parker, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also reported positive attributes including an attractive work -life balance, interesting subject matter, and an intellectually challenging fi eld (Syed et al, 2008;Wigney & Parker, 2008).…”
Section: Background Information and Literature Reviewmentioning
confidence: 99%